An Intrinsically Conductive Phosphorus-Doped Perovskite Oxide as a New Cathode for High-Performance Dye-Sensitized Solar Cells by Providing Internal Conducting Pathways - Xu, M.; Wang, Wei; Liu, Y.; Zhong, Yijun; Xu, Xiaomin; Sun, Y.; Wang, J.; Zhou, W.; Shao, Zongping (WILEY-V C H VERLAG GMBH, 2019)
State-of-the-art dye-sensitized solar cells (DSSCs) usually use the noble and scarce platinum (Pt) cathode, which strongly limits the practical applications of DSSCs. Accordingly, low-cost, highly active, and stable alternatives to Pt are highly desired. Herein, an intrinsically conductive perovskite oxide is reported as a new cathode for DSSCs using a simple nonmetal element doping strategy. The phosphorus-doped perovskite oxide (SrCo0.95P0.05O3−δ [SCP]) shows superior activity/durability for the triiodide (I3−) reduction reaction (IRR) and structural stability relative to the parent compound (SrCoO3−δ [SC]) due to the greatly enhanced electrical conductivity and the stabilization of the perovskite structure. The internal conducting pathways are demonstrated to be very important to obtain high IRR activity of the perovskite cathode, even when the cathode is incorporated with conductive multiwalled carbon nanotubes (MWCNTs). The DSSC with the N719 dye and SCP/MWCNTs cathode displays a superior power conversion efficiency (PCE) of 10.1% to those with Pt (8.11%) and SC/MWCNTs (6.80%) cathodes. In addition, the DSSC with the C101 dye and SCP/MWCNTs cathode shows an attractive PCE of 12.2% with an enhancement of 23%, as compared with the Pt cathode, suggesting that the SCP/MWCNTs composite can be one of the best substitutions to the Pt cathode, which can benefit the future industrialization of DSSCs.